Project-Based Ecology Learning in Vocational Training - Kostova, Zdravka (Journal of Environmental Science and Engineering Technology, 2013)
The article discusses project-based learning of ecosystems, biodiversity and pollution in a vocational school in Bulgaria. The teaching strategy based on interactive methods, information communication technologies, out-of-school observations, experiments and Power Point presentations versus teaching strategy based on lectures and information communication technologies were comparatively studied and the results were analyzed. Difficulties met by students and strategies for overcoming them were dealt with and described. The ecological concerns of students were surveyed using revised New Ecological Paradigm scale. The theoretical framework was based on constructivism, theory of multimedia learning, zone of proximal development and guided discovery.